180=(4x+7)+(2x+53)

Simple and best practice solution for 180=(4x+7)+(2x+53) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 180=(4x+7)+(2x+53) equation:


Simplifying
180 = (4x + 7) + (2x + 53)

Reorder the terms:
180 = (7 + 4x) + (2x + 53)

Remove parenthesis around (7 + 4x)
180 = 7 + 4x + (2x + 53)

Reorder the terms:
180 = 7 + 4x + (53 + 2x)

Remove parenthesis around (53 + 2x)
180 = 7 + 4x + 53 + 2x

Reorder the terms:
180 = 7 + 53 + 4x + 2x

Combine like terms: 7 + 53 = 60
180 = 60 + 4x + 2x

Combine like terms: 4x + 2x = 6x
180 = 60 + 6x

Solving
180 = 60 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
180 + -6x = 60 + 6x + -6x

Combine like terms: 6x + -6x = 0
180 + -6x = 60 + 0
180 + -6x = 60

Add '-180' to each side of the equation.
180 + -180 + -6x = 60 + -180

Combine like terms: 180 + -180 = 0
0 + -6x = 60 + -180
-6x = 60 + -180

Combine like terms: 60 + -180 = -120
-6x = -120

Divide each side by '-6'.
x = 20

Simplifying
x = 20

See similar equations:

| 88=-8(a-5) | | 3x+4=-2(x+2)-5 | | bx=ax-c | | (n+2)(n+1)(n+6)-9n^2=n^3+4(7n-1) | | (iz+2)(2z+3-i)=0 | | 12(6x-1)=120x | | 3=1-2x | | b^2-b+3=0 | | X-9+3(5x+4)=-2(x+6) | | 3(6-4x)=2(-6+9) | | 180=(5x)+(4x) | | 5x=25a | | 12x=22.50 | | 88=-8a-40 | | 12(2x-2)=132x | | xy+2x=3y | | 5x-3x(x-5)=-7+4x+12 | | 180=(6x-3)+(2x+41) | | 21a^5+211a^3b^2+10ab^4= | | (2a+2)(2a+1)= | | 12(6x-5)=132x | | 2x^3+3x^2-36x+17= | | 0.55x+.05(2-x)=.10(-9) | | X=35+0.5x | | 4k^2-17k+4=0 | | [2b-5]+1ifb=1 | | 9(4x-7)=90x | | x=2xy | | rx^2+2r^2=3 | | 10v=-8v | | 2x^2-42x+42= | | -4c-10=2(2c-5) |

Equations solver categories